Variety and on-farm seed management practices affect potato seed degeneration in the tropical highlands of Ecuador - Navarrete, I.; López, V.; Borja, R.; Oyarzún, P.; Garrett, K.A.; Almekinders, Conny J.M.; Xing, Y.; Struik, P.C.; Andrade-Piedra, J.L. (Elsevier, 2022)
CONTEXT Studies in the Andes have demonstrated that seed degeneration of potato occurred in experimental conditions, but was negligible in farmers' conditions. There are two hypotheses for this difference: (1) farmers cultivate resistant varieties, or (2) they use on-farm practices that can manage seed degeneration. Farmers may replace some of the seed saved from their fields with outside seed, but it is an open question what level of benefit farmers experience from partial replacement.